The Correlation of Students’ Vocabulary Mastery and Interest in Reading with their Writing Ability of Argumentation Text at The Eight Grade SMPN 14 Bandar Lampung - Evawati, Evawati; Surastina, Surastina; Sutrisno AB, Joko; Wahyuningsih, Sri (IJLHE: International Journal of Language, Humanities, and Education, 2020)
This study aims to describe the correlation of students’ vocabulary mastery and reading interest with the argumentation writing ability of VIII grade SMPN 14 Bandar Lampung. This research was conducted because of the reality on the ground that the ability to write arguments and mastery of vocabulary, as well as reading interest need to be developed. The method used in this research is correlational method. The techniques used in collecting research data are questionnaires and tests. Testing the research hypothesis using the correlation coefficient test, product moment and multiple correlation. Previously, the analysis prerequisite test was conducted, namely the normality and linearity tests of the data. The results of the study can be concluded that, (1) there is a positive and significant correlation of vocabulary mastery and argumentation writing ability which is indicated by a correlation coefficient of 0.662 and a coefficient of determination (r2) of 0.438 or 43.8%, (2) there is a positive and significant correlation between reading interest and argumentative writing ability, indicated by a correlation coefficient of 0.766 and a coefficient of determination (r2) of 0.587 or 58.7%, (3) there is a positive and significant correlation between vocabulary mastery and reading interest with writing ability argumentation shown by the correlation coefficient of 0.804 and the coefficient of determination (r2) of 0.646 or 64.6%.